Following are the abstracts from the Fourth Annual Meeting of the Society for Molecular Imaging (Molecular Imaging)
Declaration of Financial Interests or Relationships To insure balance, independence, objectivity and scientific rigor in all CME programs it is the policy of the meeting's joint sponsors that any speaker or poster presenter who makes a presentation at a program designated for AMA Physician's Recognition Award (PRA) Category 1 or 2 credit must disclose any real or apparent financial interest or other relationship (i.e., grants, research support, consultant, honoraria) that the presenter may have with the manufacturers, distributors or providers of any commercial products or services that may be discussed in the presentation. ISMRM and SMI do not imply that such financial interests or relationships are inherently improper or that such interests or relationships would prevent the presenter from making an objective presentation. However, it is imperative that such financial interests or relationships be identified by the presenter so that participants at the CME activity may have these facts fully disclosed prior to the presentation, and may form their own judgments about the presentation. Towards this end, the information provided by each presenter can be found at the bottom of each abstract. Every speaker, abstract presenter, organizer or anyone else who has control over any content in this meeting has been required to submit a Declaration of Financial Interests or Relationships, even if there is no conflict or relationship to declare.